Effect of Vitamin B(12) and Folate on Homocysteine levels in colorectal cancer - Chandy, Sunil (Springer-Verlag, 2008)
Folate and cobalamin (Vitamin B(12)) are two essential micronutrients involved in one-carbon metabolism, which affects heart disease, neural tube defects and cancer. Methylenetetrahydrofolate reductase, the key enzyme involved in one carbon metabolism produces methyl tetrahydrofolate from methylene tetrahydrofolate, which in turn donates methyl group to homocysteine to generate methionine. There exist two common low function polymorphic variants of the methylenetetrahydrofolate reductase gene involving nucleotides 677 C→T and 1298 A→C, which are associated with hyperhomocysteinemia. These polymorphisms are also linked with increased risk for certain cancers such as breast cancer and at the same time providing a protective effect on colorectal cancer. In this case control study, we have evaluated levels of folic acid, vitamin B(12) and homocysteine in patients with colorectal cancer. Folate and homocysteine levels did not differ significantly between the two groups; however an increasing trend was noticed with increase in homocysteine levels. Vitamin B(12) levels were increased in cases compared to control group.